A Pragmatic Study of Request Head Acts and External Modifications as Seen in "Frozen" - Reri Rahmat Riyadi Putra (Lexicon, 2014)
This research attempts to investigate the requests in Frozen, an American 3D computer-animated musical fantasy-comedy film. The data comprise 76 requests collected from the subtitles of the movie, along with the context. Specifically, it aims to classify and analyze the requests‘ head acts and external modifications, and to find out the more dominant strategy appears in the movie. The classification of the head act was according to the theory of request strategies proposed by Blum-Kulka and Olshtain (1984): direct, conventionally indirect, and non-conventionally indirect. The classification of the external modification was according to the theory of external modification strategies proposed by Blum-Kulka, House and Kasper‘s classification (qtd. in Schauer, 92): preparator, grounder, disarmer, imposition minimizer, sweetener, and promise of reward. Based on the classification, it can be seen that direct strategies is the most preferred strategies in uttering requests with 50 (65.79%) occurrences and grounder is the most preferred strategies in modifying requests with 23 (67.65%) occurrences. The high frequency of direct strategy might be caused by the characters‘ intimacy in the storyline and grounder might be caused by the easiness of using grounder in modifying requests.